GERIATRIC REHABILITATION - Şebnem Koldaş; Şehim Kutlay (Archives of Rheumatology, 2002)
Geriatric rehabilitation has gained importance as the mean life time has increased with the recent developments in science, technology and health. Geriatric rehabilitation can be defined as solving the problems of physiological elderness, minimizing disease or disability and improving the physiological, psychosocial and economic independence of elder people in their daily life. In order to achieve geriatric rehabilitation, one must know the physiological changes occuring in elderness, determine the associated problems and choose the most appropriate rehabilitation method.